On Destination Logo: A Design Review of Visit Malaysia Year’s Logo (1990 -2020) - ShawHong SER (Bina Nusantara University, 2022)
Similar to companies and organizations across the globe, countries as well engage in branding strategies to establish a brand identity and to be positioned as major tourist destinations. Thereupon, the destination logo as one of the most significant elements of a country’s branding has become an important subject for brand design and communication research. In this paper, to respond to the research scholarly interest in communication design, the researcher has made an attempt to provide a design review of Malaysia’s destination logo from 1990 to 2020. Based on destination logos employed by Malaysia Tourism Promotion Board, the researcher examined how different logos have been designed to represent Malaysia as an outstanding tourism destination along with the development of the “Visit Malaysia Year” (VMY) tourism campaigns. As aforementioned, this paper will provide insights into an understanding of the design and development of destination logos in Malaysia.